Nursing's Role in Successful Stroke Care Transitions Across the Continuum: From Acute Care Into the Community. Issue 12 (December 2021) - Camicia, Michelle; Lutz, Barbara; Summers, Debbie; Klassman, Lynn; Vaughn, Stephanie
Abstract : Facilitating successful care transitions across settings is a key nursing competency. Although we have achieved improvements in acute stroke care, similar advances in stroke care transitions in the postacute and return to community phases have lagged far behind. In the current delivery system, care transitions are often ineffective and inefficient resulting in unmet needs and high rates of unnecessary complications and avoidable hospital readmissions. Nurses must use evidence-based approaches to prepare stroke survivors and their family caregivers for postdischarge self-management, rehabilitation, and recovery. The purpose of this article is to provide evidence on the important nursing roles in stroke care and transition management across the care continuum, discuss cross-setting issues in stroke care, and provide recommendations to leverage nursing's impact in optimizing outcomes for stroke survivors and their family unit across the continuum. To optimize nursing's influence in facilitating safe, effective, and efficient care transitions for stroke survivors and their family caregivers across the continuum we have the following recommendations (1) establish a system of coordinated and seamless comprehensive stroke care across the continuum and into the community; (2) implement a stroke nurse liaison role that provides consultant case management for the episode of care across all settings/services for improved consistency, communication and follow-up care; (3) implement a validated caregiver assessment tool to systematically assess gaps in caregiver preparedness and develop a tailored caregiver/family care plan that can be implemented to improve caregiver preparedness; (4) use evidence-based teaching and communication methods to optimize stroke survivor/caregiver learning; and (5) use technology to advance stroke nursing care. Nurses must leverage their substantial influence over the health care delivery system to achieve these improvements in stroke care delivery to improve the health and lives of stroke survivors and their families.